Resistance of In2О3–p-InSe photoconverter to different types of irradiation - Сидор, Олег Миколайович (Eastern-European Journal of Enterprise Technologies, 2012)
The article presents the results of irradiation of In2O3–p-InSe photoconverters by braking γ-quanta, high-energy electrons and gamma-neutrons. In particular, their electrical and photoelectrical parameters were analyzed. The latest were compared to the similar parameters of test solar IТО–SiO2–n-Si element. For the initial doses, depending on the type of irradiation, the major changes consisted in: - the improvement of the rectification factor K at 10-100% and the monochromatic volt-watt sensitivity SU at 18-44%; - the maintenance or increase of voltage of idle running Uхх; - the increase of the short-circuit current Jкз at 7% ( under the action of gamma-neutrons and electrons) and the monochromatic ampere-watt sensitivity of SI at 11-28% ( under the action of γ-quanta and electrons). In other cases, the listed parameters have been experiencing the minimal decline (up to 5%). The imperfection coefficient ВАХ n has remained constant or has even slightly improved (under the action of gamma-neutron). With further radiation, it was fixed: values ​​ Uхх, Jкз, SU and SI were saved in case of γ-quanta; Uхх and SU increased under the action of electrons, K value was significantly improved and Uхх was unchanged in case of gamma neutrons. The decline of the rest of the parameters was in the range 2-12%. The specific changes in the spectral contours of photoresponse were not detected (except the irradiation by electrons). The possible mechanisms of radiation damages were discussed. In case of γ- and electron radiation, this is the generation of point defects - Frenkel pairs, in case of neutron radiation - formation of vacancy and internodal clusters. At the same time, the used doses and types of radiation have caused severe damage of IТО–SiO2–n-Si structure